Reproductive cycle, sexual maturity and longevity ofOdontophrynus americanus(Anura: Odontophrynidae) in South Brazil - Brum, Amanda J. C.; Loebens, Luiza; Prado, Cynthia P. A. [UNESP]; Cechin, Sonia Z. (Wiley-Blackwell, 2020)
Studies on the reproductive biology and age of amphibians provide primary information about the life history and population demographic parameters of species. Here, we describe the reproductive cycle, size-fecundity relationships, reproductive effort, sexual dimorphism and sexual maturity ofOdontophrynus americanus,the flood frog, from South Brazil. A total of 96 individuals were analysed. The reproductive cycles of males and females were described through morphoanatomical analysis of testis and ovary. Age at onset of sexual maturity and estimated longevity were determined by skeletochronology. Individuals ofO. americanuspresented a potentially continuous reproductive cycle with a peak of reproductive activity in the warmer months. Females presented a higher reproductive investment than males. Sexual maturity was reached at around one year of age for both sexes while longevity differed between the sexes, with females living up to six years and males up to ten years. No evidence of sexual size dimorphism was found. This study is among the few that have assessed age at sexual maturity and longevity in a Neotropical anuran. Basic aspects of life history are of paramount importance because they allow comparisons and test of hypotheses to be made, which can help to build generalizations about the evolutionary meaning of ecological strategies.
Keywords: amphibian; flood frog; gametogenesis; reproductive biology; skeletochronology